Characterization of Cer-1 cis-regulatory region during early Xenopus development - Silva, Ana Cristina; Filipe, Mário; Steinbeisser, Herbert; Belo, José António (Development genes and evolution, 2011)
Cerberus-related molecules are well-known Wnt, Nodal, and BMP inhibitors that have been implicated in different processes including anterior-posterior patterning and left-right asymmetry. In both mouse and frog, two Cerberus-related genes have been isolated, mCer-1 and mCer-2, and Xcer and Xcoco, respectively. Until now, little is known about the mechanisms involved in their transcriptional regulation. Here, we report a heterologous analysis of the mouse Cerberus-1 gene upstream regulatory regions, responsible for its expression in the visceral endodermal cells. Our analysis showed that the consensus sequences for a TATA, CAAT, or GC boxes were absent but a TGTGG sequence was present at position −172 to −168 bp, relative to the ATG. Using a series of deletion constructs and transient expression in Xenopus embryos, we found that a fragment of 1.4 kb of Cer-1 promoter sequence could reproduce the endogenous expression pattern of Xenopus cerberus. A 0.7-kb mcer-1 upstream region was able to drive reporter expression to the involuting mesendodermal cells, while further deletions abolished reporter gene expression. Our results suggest that although no sequence similarity was found between mouse and Xenopus cerberus cis-regulatory regions, the signaling cascades regulating cerberus expression, during gastrulation, is conserved.